The Role of Innovation in the Competition Between Fintechs and Traditional Banks in Brazil - Schreiber, Dusan; Viana, Luciane Pereira; Gribler, Francini Manoela (Archives of Business Research, 2024)
The Brazilian banking market has distinct and peculiar characteristics, resulting from its historical evolution, specific cultural traits and control exercised by the Central Bank. This article aims to analyze, from the perspective of one of the largest Brazilian banks, the role of innovation, products and processes, in the competition between fintechs and traditional banks. The methodology used was a single case study, qualitative and descriptive approach, with data collection through interviews with managers and customers of Alfa Bank and internal and external documentary survey. It has been evident that the emergence of Fintechs, with its flexible business model, with reduced operational costs, provided by product and process innovation, impacted the banking market in Brazil, traditionally dominated by a small number of large banks, which operated in a traditional way. The analyzed bank, known as Alfa, follows technological developments and improves its main products and services, taking into account suggestions from both employees and customers. The results also showed that Brazilian customers recognize the importance of innovation, especially technology-based, but also value the physical presence of traditional banks, which inspires more confidence in them than Fintechs, which operate online.